Microaerophilic Fe‐oxidizing micro‐organisms in Middle Jurassic ferruginous stromatolites and the paleoenvironmental context of their formation (Southern Carpathians, Romania). Issue 3 (15th January 2020) - Grădinaru, Mihaela; Lazăr, Iuliana; Ducea, Mihai N.; Petrescu, Lucian
Abstract: Ferruginous stromatolites occur associated with Middle Jurassic condensed deposits in several Tethyan and peri‐Tethyan areas. The studied ferruginous stromatolites occurring in the Middle Jurassic condensed deposits of Southern Carpathians (Romania) preserve morphological, geochemical, and mineralogical data that suggest microbial iron oxidation. Based on their macrofabrics and accretion patterns, we classified stromatolites: (1) Ferruginous microstromatolites associated with hardground surfaces and forming the cortex of the macro‐oncoids and (2) Domical ferruginous stromatolites developed within the Ammonitico Rosso ‐type succession disposed above the ferruginous microstromatolites (type 1). Petrographic and scanning electron microscope (SEM) examinations reveal that different types of filamentous micro‐organisms were the significant framework builders of the ferruginous stromatolitic laminae. The studied stromatolites yield a large range of δ 56 Fe values, from −0.75‰ to +0.66‰ with predominantly positive values indicating the prevalence of partial ferrous iron oxidation. The lowest negative δ 56 Fe values (up to −0.75‰) are present only in domical ferruginous stromatolites samples and point to initial iron mobilization where the Fe(II) was produced by dissimilatory Fe(III) reduction of ferric oxides by Fe(III)‐reducing bacteria. Rare‐earth elements and yttrium (REE + Y) are used to decipher the nature of the seawater during the formation of the ferruginous stromatolites. Cerium anomalies display moderate to small negative values for the ferruginous microstromatolites, indicating weakly oxygenated conditions compatible with slowly reducing environments, in contrast to the domical ferruginous stromatolites that show moderate positive Ce anomalies suggesting that they formed in deeper, anoxic–suboxic waters. The positive Eu anomalies from the studied samples suggest a diffuse hydrothermal input on the seawater during the Middle Jurassic on the sites of ferruginous stromatolite accretion. This study presents the first interpretation of REE + Y in the Middle Jurassic ferruginous stromatolites of Southern Carpathians, Romania.